2013
DOI: 10.1177/0022034513488393
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous and Compound Heterozygous MMP20 Mutations in Amelogenesis Imperfecta

Abstract: In this article, we focus on hypomaturation autosomal-recessive-type amelogenesis imperfecta (type IIA2) and describe 2 new causal Matrix metalloproteinase 20 (MMP20) mutations validated in two unrelated families: a missense mutation p.T130I at the expected homozygous state, and a compound heterozygous mutation having the same mutation combined with a nucleotide deletion, leading to a premature stop codon (p.N120fz*2). We characterized the enamel structure of the latter case using scanning electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 27 publications
4
31
0
1
Order By: Relevance
“…We reviewed literatures regarding AI clinical phenotypes, enamel ultrastructure and the disease-causing gene mutations, and tried to establish the correlation among them (see Table II) 2,18,[20][21][22][23][24][25][26][27][28][29][30][31][32] . From the literatures review and our study, no specific correlation among the clinical phenotypes, ultrastructure and gene mutations was found for AI patients.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed literatures regarding AI clinical phenotypes, enamel ultrastructure and the disease-causing gene mutations, and tried to establish the correlation among them (see Table II) 2,18,[20][21][22][23][24][25][26][27][28][29][30][31][32] . From the literatures review and our study, no specific correlation among the clinical phenotypes, ultrastructure and gene mutations was found for AI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Non-syndromic AI is caused by mutations in genes encoding major enamel matrix proteins: amelogenin ( AMELX ) [2, 3], enamelin ( ENAM ) [4, 5], ameloblastin ( AMBN ) [6], enamelysin ( MMP20 ) [7, 8] and kallikrein 4 ( KLK4 ) [9]. In addition, mutations in the FAM83H , C4orf26 , WDR72 and SLC24A4 genes have been identified to cause non-syndromic AI with various phenotypes [10-15].…”
Section: Introductionmentioning
confidence: 99%
“…Human and mouse mutations in both MMP20 (Caterina et al, 2002; Kim et al, 2005; Ozdemir et al, 2005; Lee et al, 2010; Gasse et al, 2013) and KLK4 (Hart et al, 2004; Simmer et al, 2009; Wang et al, 2013) cause severe enamel malformations and therefore demonstrate that no other proteinase has an extensive overlapping function with either of these proteinases. If this were the case, no severe enamel phenotype would likely occur if the activity of MMP20 or KLK4 were compromised.…”
Section: Enamel Proteinasesmentioning
confidence: 99%
“…The precise function of these proteins remains unclear. However, human mutations in AMELX (Hu et al, 2012), ENAM (Rajpar et al, 2001), and MMP20 (Kim et al, 2005; Ozdemir et al, 2005; Lee et al, 2010; Gasse et al, 2013) genes and mouse knockout models (Gibson et al, 2001; Caterina et al, 2002; Fukumoto et al, 2004; Masuya et al, 2005; Seedorf et al, 2007; Hu et al, 2008) have definitively demonstrated that each of these proteins are absolutely required for proper enamel formation. This conclusion is supported by the observation that the genes encoding secretory stage enamel proteins are consistently pseudogenized in vertebrates that have lost the ability to make teeth, or specifically dental enamel, during evolution (Meredith et al, 2009, 2011, 2013).…”
Section: Introductionmentioning
confidence: 99%